The Effect of Supply Chain Management on the Competitiveness of the Telecommunications Industry in Zimbabwe - Garikai Mlambo; Dr. Vusumuzi Sibanda; Shakerod Munuhwa (International Journal of Engineering and Management Research, 2020)
The purpose of this study was to analyse the impact of supply chain management (SCM) on the competitiveness of the telecommunications industry in Zimbabwe. The objectives of the study were to figure out the extent to which SCM contributes to organisational competitive advantage in the telecommunications industry in Zimbabwe, to determine the level of bargaining power when making local and off shore purchases, the extent of risk exposure due to global transactions and finally, to ascertain the strategies used on supplier ratings. Interviews and questionnaires were used as the main instruments for data collection. Questionnaires were distributed to 50 respondents with 36 responding, representing a 72 percent response rate. Data were analysed using SPSS and the results presented in graphs and tables. Interviews were carried out using a structured interview guide for uniformity of questions being asked. Three interviews were conducted with procurement managers from the three organisations represented namely; Econet, TelOne and NetOne. The results showed that SCM is a strong contributor to organisational competitiveness. If organisations in the telecommunications sector prudently apply SCM policies, strategies and practices, the performance in terms of profitability realised and competitive advantage will increase. Recommendations are that quality of products; better supplier management and competitive pricing may be realised if firms can adopt SCM principles and practices.